Tulang Fauna Vertebrata di Situs Gua Kidang, Blora, Jawa Tengah - Hidayatullah, Ghufron (Paradigma: Jurnal Kajian Budaya, 2017)
The research discusses the utilization of vertebrate fauna at the Kidang Cave site to identify the types and variations of vertebrate animals as subsistence and their respective habitats. The analysis was also instrumental in defining the natural landscape of Kidang Cave during the prehistoric era. Faunal fragments were previously analyzed and identified taxonomically and anatomically. The analysis started with re-sortation of faunal bone fragments, classifying and further analyzing the data to obtain the number of identified specimens for each taxon (NISP) and the minimum number of individuals (MNI). From 8,265 bone fragments, only 1,378 were anatomically and taxonomically identifiable. The MNI calculation revealed a number of 23 taxa that were identified down to their familial levels and only two to class levels. The result of this research identified that various fauna from different habitats were part of the human diet. Based on this analysis, the natural environment surrounding Kidang Cave during the prehistoric era was then predicted.